A Precessing Jet Scenario for the Multi-Wavelength Long-Term Modulation of LS I +61°303 - Frédéric Jaron (Universe, 2021)
The high-mass X-ray binary LS I +61°303 is detected across the electromagnetic spectrum from radio until the very high energy <semantics>γ</semantics>-ray regime. The emission is not only highly variable on many time scales, but is also periodic at all observed wavelengths. Periodic modulation was observed on different time-scales, ranging from hours, over months to several years. The subject of this article is a super-orbital, long-term modulation of ∼4.6 years. We review the observation of this periodic modulation at multiple wavelengths and investigate systematic relationships between them. IN particular, radio observations reveal that the long-term modulation is a very stable feature of the source. Observations at other wavelengths result in a phase-shift of the modulationpattern that is a systematic function of energy. The stability of this period favors a scenario in which the long-term modulation is the result of a precessing jet giving rise to periodic changes in the Doppler factor, beating with the orbital modulation of the accretion rate. We explain the phase-shifts across energy bands in a scenario with shorter wavelengths originating closer to the base of the presessing jet. A significant deviation of the TeV emission from this trend possibly requires a different explanation related to magnetic reconnection events.